Dressed to kill? Visible markers of coalitional affiliation enhance conceptualized formidability. Issue 3 (5th February 2016) - Fessler, Daniel M. T.; Holbrook, Colin; Dashoff, David
Abstract : Displaying markers of coalitional affiliation is a common feature of contemporary life. In situations in which interaction with members of rival coalitions is likely, signaling coalitional affiliation may simultaneously constitute an implicit challenge to opponents and an objective commitment device, binding signalers to their coalitions. Individuals who invite conflict, and who cannot readily back out of conflict, constitute a greater threat than those who avoid conflict and preserve the option of feigning neutrality. As a consequence, the former should be viewed as more formidable than the latter. Recent research indicates that relative formidability is summarized using the envisioned physical size and strength of a potential antagonist. Thus, individuals who display markers of coalitional affiliation should be conceptualized as more physically imposing than those who do not. We tested this prediction in two experiments. In Study 1, conducted with U.S. university students, participants inspected images of sports fans' faces. In Study 2, conducted with U.S. Mechanical Turk workers, participants read vignettes depicting political partisans. In both studies, participants estimated the physical formidability of the target individuals and reported their own ability to defend themselves; in Study 2, participants estimated the target's aggressiveness. Consonant with predictions, targets depicted as signaling coalitional affiliation in situations of potential conflict were envisioned to be more physically formidable and more aggressive than were those not depicted as signaling thusly. Underscoring that the calculations at issue concern the possibility of violent conflict, participants' estimates of the protagonist's features were inversely correlated with their ability to defend themselves. Aggr. Behav. 42:299–309, 2016. © 2016 Wiley Periodicals, Inc.